The Theme of the Polish Minority in Latgalian Press (1920–1934) - Malahovskis, Vladislavs (Acta humanitarica academiae Saulensis, 2021)
The article aims to reveal the position of the Latgalian press in the formation of the inhabitants’ public opinion of the Polish minority in Latgale (1920–1934). The basis of the research consists of around 50 articles published in the Latgalian newspapers. The research is based on the analysis of qualitative data, discourse-historical approach, using the detaching discursive construction of “we”–“they”, e.g., in the context of the article – “the Latgalians” – “the Polish”.In the early 1920s, the newspaper articles related to the Polish, mostly to the nobility, desiring to return the old good times, when the Polish was the dominating social group in Latgale. In the following years, the Polish were largely reflected as a minority disloyal to Latgalians and hostile to the Latvian state based on this ground. In many cases, the publications about the Polish minority are contradictory; while creating a negative image of the Polish, they are also called ‘faith brothers’ and thereby – allies.
Keywords: Poles; Latgalians; Latgalian press; Latgale